Evaluation of Biogenic Volatile Organic Compound Emissions and Its Impact of Ozone Formation - Kondo, A.; Hai, B.; Shrestha, K. L.; Kaga, A.; Inoue, Y. (Journal of the Institute of Engineering, 2009)
The standard Biogenic Volatile Organic Compound (BVOC) emissions from ten Japanese plant species were measured by using a growth chamber where temperature and light intensity can be controlled. These species were selected due to their abundance in the estimated domain of the Kinki region. The BVOC emissions in Kinki region during July 2002 were estimated by revising the standard BVOC emissions from temperature and light intensity which were calculated by MM5. The two types of the ozone calculation were carried out by CMAQ. One was the calculation with BVOC emissions (BIO). Another was the calculation that assumes BVOC emissions to be zero (NOBIO). The maximum ozone concentrations of BIO reasonably reproduced the observed maximum concentrations in especially the fine days. The hourly differences of monthly average ozone concentrations between BIO and NOBIO had the maximum value of 6ppb at 2 p.m. The explicit difference appeared in urban area, though the place where the maximum of difference occurred changed. It was shown that the BVOC emitted from the forest area strongly affected the ozone generation in the urban area. Key words: biogenic volatile organic compound, ozone, MM5, CMAQ, growth chamber Journal of the Institute of Engineering, Vol. 7, No. 1, 2009, July, pp. 48-55 doi: 10.3126/jie.v7i1.2062